Cycloaddition reactions for antiviral compounds - Quadrelli, Paolo (Modern Applications of Cycloaddition Chemistry, 2019)
Prominent in the current stage of drug development, antiviral compounds can be efficiently prepared through cycloaddition reactions. The chapter reports the use of classical Diels–Alder and their hetero version for the design and synthesis of compounds that were tested for their antiviral activities against a variety of viruses. Furthermore, 1,3-dipolar cycloaddition reactions of selected 1,3-dipoles, such as azides, nitrones, and nitrile oxides, are reviewed in the light of their application in the preparation of key intermediates for antiviral synthesis. A few examples of [2+2] cycloaddition reactions are also presented. The products obtained from these pericyclic reaction approaches were all tested for their activities in terms of blocking the virus replication, and the relevant biological data are highlighted.